The Effectiveness of Gamification in Enhancing English Language Learning Outcomes - Putri Fachri Aulia Fatah (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study investigates the effectiveness of gamification in enhancing English language learning outcomes among learners. Gamification, defined as the integration of game elements such as points, badges, leaderboards, and challenges into non-game settings, has gained widespread popularity as an innovative and motivating instructional approach in education. The primary goal of this research is to evaluate how gamified strategies impact learner engagement, motivation, and overall language proficiency in English classrooms. To achieve this, a quasi-experimental design was employed, involving two groups of learners: an experimental group exposed to gamified learning activities and a control group receiving traditional instructional methods. Data collection included pre- and post-assessments on language skills, as well as surveys measuring learners’ motivation and engagement levels. Analysis of the collected data reveals that the group learning through gamification demonstrated significantly higher gains in language proficiency compared to the control group. Additionally, the gamified group reported enhanced motivation and participation, indicating that gamification positively influences learners’ attitudes toward language learning. These findings suggest that incorporating game elements into English language teaching can create more dynamic, interactive, and enjoyable learning environments. Gamification not only fosters cognitive development but also satisfies psychological needs such as autonomy, competence, and relatedness, which are essential for sustaining motivation. Therefore, this study supports the use of gamified pedagogy as a promising tool to improve educational outcomes, particularly in language acquisition. Future research is encouraged to explore long-term effects and optimal design strategies for gamified learning applications.